1985
DOI: 10.1152/jn.1985.54.3.479
|View full text |Cite
|
Sign up to set email alerts
|

Processing of vibrissa sensory information within the rat neocortex

Abstract: Neuronal response properties were compared among different layers of the urethan-anesthetized rat vibrissa cortex. Measurements were made of the receptive-field (RF) size, the degree of directional selectivity, the latency of driving, the velocity threshold, and the tuning-curve slope. The RF size was defined by the number of whiskers that, when deflected individually, activated a neurons. For the center whisker of the RF (usually whisker C3), the response to deflection in the most preferred direction was comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
59
4

Year Published

1987
1987
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(79 citation statements)
references
References 0 publications
16
59
4
Order By: Relevance
“…Therefore, although at all stimulus intensities Gr cells had the earliest and steepest response, the dV/dt of IGr cells was the most sensitive to changes in velocity-acceleration. This result is consistent with the high velocity thresholds reported for layer 5 neurons (Ito, 1985(Ito, , 1992.…”
Section: Characteristics Of the Response At Rest To Increasing Stimulsupporting
confidence: 92%
See 1 more Smart Citation
“…Therefore, although at all stimulus intensities Gr cells had the earliest and steepest response, the dV/dt of IGr cells was the most sensitive to changes in velocity-acceleration. This result is consistent with the high velocity thresholds reported for layer 5 neurons (Ito, 1985(Ito, , 1992.…”
Section: Characteristics Of the Response At Rest To Increasing Stimulsupporting
confidence: 92%
“…In the rodent barrel system, neurons are exquisitely sensitive to velocity (Gibson and Welker, 1983;Ito, 1985;Shoykhet et al, 2000;Deschenes et al, 2003;Temereanca and Simons, 2003;Lee and Simons, 2004) and acceleration (Temereanca and Simons, 2003) at which the corresponding principal whisker in the mystacial pad is deflected. As rodents explore, their whiskers repetitively move back and forth at 5-15 Hz (Welker et al, 1964;Carvell and Simons, 1995;Berg and Kleinfeld, 2003) contacting surfaces and objects, causing small angular deflections at the base of the whiskers.…”
Section: Introductionmentioning
confidence: 99%
“…6,25 However, other studies have failed to find a difference in RF size in layer IV and have concluded that RF size is independent of the laminar location of the recorded neuron. 18 Interestingly, hourglass-shaped IOS patterns were observed in the present study following layer IV and V stimulation, but not following stimulation delivered at the layer VI/WM border, a location usually chosen for allowing the most physiological stimulation of cortex. The difference between functional hourglass and columnar patterns recorded in vivo could be due to differences in anesthetic or stimulus conditions among studies.…”
Section: Comparison With Other Anatomical Neurophysiological and Opcontrasting
confidence: 42%
“…For example, a peak of supralinear summation was found in layers II/III (Shimegi et al 1999), and facilitatory interactions were also found in layer V (Ghazanfar and Nicolelis 1997). In parallel, anatomical data have confirmed the lack of intracortical horizontal connections between barrels in layer IV and their predominance in nongranular layers, where they could be the basis for multi-whisker integration (Gottlieb and Keller 1997;Ito 1985;LĂŒbke et al 2000;Petersen and Sakmann 2000). These last observations, as well as electrophysiological recordings and optical imaging studies investigating functional circuitry (Goldreich et al 1999;Laaris and Keller 2002;Petersen and Sakmann 2001;, have contributed massively to the idea that barrels in layer IV function independently of one another, i.e., activity from one barrel does not spread directly to an adjacent barrel.…”
Section: Influence Of the Cortical Layermentioning
confidence: 83%